Biomarkers in mangrove root crab Goniopsis cruentata for evaluating quality of tropical estuaries - Davanso, Marcela Bergo; Moreira, Lucas Buruaem; Pimentel, Marcionília Fernandes; Costa-Lotufo, Letícia Veras; Abessa, Denis Moledo de Souza (Elsevier, 2013)
The present study reports the use of biomarkers analyzes in mangrove root crab Goniopsis cruentata tissues to assess the environmental quality of two tropical estuarine areas. Animals from Ceará River estuary presented inhibition of ChE and GST enzymatic activities and higher rates of DNA damage with respect to those sampled in a pristine environment. G. cruentata appears to represent a proper species to monitor the quality of tropical estuaries. Since Ceará River is a legally protected area, this survey highlight the needs to implement actions to control pollution loads and improve the protection of natural ecosystems and resources. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Cholinesterase; Coastal zone; Contamination; Crabs; DNA damage; Estuary; Glutathione-S-transferase; Protected area